1982
DOI: 10.7863/jum.1982.1.9.367
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound biologic effects: a suggestion of strain specificity.

Abstract: Pregnant hybrid LAF 1 /j mice were exposed to continuous-wave ultrasonic energy at a frequency of 1 MHz at a spatial peak intensity of either 2.5 W/cm 2 or 0 W/cm 2 (sham) for 20 seconds on the eighth day of gestation. Fetal weight (day 18 of gestation) and postpartum pup weight (21, 29 and 42 days post conception) were determined. No significant differences in weight were observed. This result differs from findings in others studies using outbred mouse strains. It is suggested that hybrid mice exposed to ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Fetal weight is thought to be one of the most sensitive indicators of embryotoxicity; is a common effect following in utero exposure to a variety of insults, including intrauterine heating or maternal stress (reviewed in Carnes et al 1995), and has been reported in different mouse strains (Stolzenberg et al 1980a(Stolzenberg et al , 1980bTarantal et al 1993). It has been suggested that there may be strain differences in the effects of US in mice (O'Brien et al 1982;Kim et al 1983). Also, weaning weights are affected by smaller litter size because weights of the young are known to depend on the number of pups being reared (reviewed in Carnes et al 1995), but no significant differences in litter size were observed for any exposure group.…”
mentioning
confidence: 97%
“…Fetal weight is thought to be one of the most sensitive indicators of embryotoxicity; is a common effect following in utero exposure to a variety of insults, including intrauterine heating or maternal stress (reviewed in Carnes et al 1995), and has been reported in different mouse strains (Stolzenberg et al 1980a(Stolzenberg et al , 1980bTarantal et al 1993). It has been suggested that there may be strain differences in the effects of US in mice (O'Brien et al 1982;Kim et al 1983). Also, weaning weights are affected by smaller litter size because weights of the young are known to depend on the number of pups being reared (reviewed in Carnes et al 1995), but no significant differences in litter size were observed for any exposure group.…”
mentioning
confidence: 97%
“…forent hiologi<. "al conditions in a dilforcnt hut similar system, O'Brien et al 22 and Kim et uJ.2. 1 lcmnd that exposure of LAF 1 /J hybrid 111 ice al a spatial peak (SP) intensity of 2.5 W/cm 2 {l M 1-J,,;) for 20 seconds die!…”
Section: Experiments During Organogenesismentioning
confidence: 99%
“…O'Brien ct al. 22 suggested that hyhricl mice may he more resistant than outbred mice lo weight reduction. It should be noted, however, that the experiments were not contemporaneous ancl that fotuses derived from matings of hyhrid parents have varied mul complex genetic constitutions.…”
Section: Experiments During Organogenesismentioning
confidence: 99%